Banking crises in emerging economies: Can credit variables work as early warnings? - Martina Jašová (Charles University in Prague, Institute of Economic Studies (IES), 2015)
This paper explores the role of private credit variables as early warning indicators (EWIs) of banking crises in context of emerging economies. The performance is evaluated by using receiver operating characteristics (ROC) curve and area under the curve (AUC) on long series on credit to the private non-financial sector. The results suggest that credit-to-GDP gap as proposed by Basel III may not be the best performing indicator to signal future banking distress in case of emerging economies. Credit growth outperforms credit-to-GDP gap in all time horizon. These findings are particularly important as they challenge the literature published on EWIs in emerged economies and highlight the need to use complementary indicators and multivariate analysis especially in the environment of emerging economies.
Keywords: C33; G01; G28; 330; Early warning indicators; credit-to-GDP; countercyclical capital buffer; emerging markets; ROC; area under the curve